Democracy and Truth: A Short History by Sophia Rosenfeld (A Book Review) - Gröppmaier, Sakina Shakil (Review of International American Studies, 2020)
Rosenfeld, Sophia. Democracy and Truth: A Short History, University of Pennsylvania Press, 2019. ISBN13: 9780812250848 -- a book review by Sakina Shakil Gröppmaier